JUDICIAL AND LEGAL INTERVENTION IN CHIEFTAINCY LAW AND ADMINISTRATION IN NIGERIA: IMPLICATION FOR POLICY - T. Kehinde Adekunle (African Journal of Educational Management, 2021)
In recent times, chieftaincy disputes constitute a string of common legal phenomenon which is spreading like a wild-fire among the numerous ethnic groups in Nigeria and they form some of the cases now being filed ceaselessly in our courts on daily basis. Actually, besides land disputes, there is hardly any other dispute in some judicial divisions of our court which surpasses chieftaincy wrangling in number. A reason for this trend of event in the different Nigerian localities is probably the prestige and honour that chiefs usually attract in the society. Such honour and prestige even assume a larger-than-life image when a person is installed as an “Emir”, “Igwe”, “Oba” or “Obi”.1 It appears that this phenomenon cuts across all African countries. It is not peculiar to Nigeria. After all, everybody wants honour, prestige, power and respect. Another reason for the high spate of litigations in respect of chieftaincy matters is the numerous spoils of office which the holder of chieftaincy title stands to benefit or receive from his subjects from time to time. Such gifts come in various forms and include land, money, food, chattels and even women on some occasions. The booties attach a lot of glamour to the office of a Chief and that, in turn, “inspires” the contenders for chieftaincy titles to struggle endlessly to occupy vacant chieftaincy stools. To be candid, it is a struggle that may never know an end in the African community. For as long as human beings exist, Nigerians and, indeed, Africans will continue to attach a high sense of value to chieftaincy titles.